2022
DOI: 10.3390/ijms23179850
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Liver Sieve: The Interplay between Actin and Myosin Regulatory Light Chain Regulates Fenestration Size and Number in Murine Liver Sinusoidal Endothelial Cells

Abstract: Liver sinusoidal endothelial cells (LSECs) facilitate the efficient transport of macromolecules and solutes between the blood and hepatocytes. The efficiency of this transport is realized via transcellular nanopores, called fenestrations. The mean fenestration size is 140 ± 20 nm, with the range from 50 nm to 350 nm being mostly below the limits of diffraction of visible light. The cellular mechanisms controlling fenestrations are still poorly understood. In this study, we tested a hypothesis that both Rho kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…However, this does not mean, of course, that high-dose cytochalasan effects are restricted to the inhibition of RhoA signaling and myosin II-based contractility. This notion is consistent with the fact that contractility inhibition by Y27632 (a Rho-kinase inhibitor), blebbistatin (myosin II inhibitor), or ML7 (myosin light-chain kinase inhibitor) each displayed effects additive to CB (1) [75]. In any case, the results indicated that an increased drug concentration causes morphological changes ranging from inhibition of membrane ruffling to the induction of cell rounding, with the only exception of chaetoglobosin K (ChK, 59) being ineffective on the latter.…”
Section: Correlating Cytochalasan Chemodiversity With the Activity Sp...supporting
confidence: 81%
“…However, this does not mean, of course, that high-dose cytochalasan effects are restricted to the inhibition of RhoA signaling and myosin II-based contractility. This notion is consistent with the fact that contractility inhibition by Y27632 (a Rho-kinase inhibitor), blebbistatin (myosin II inhibitor), or ML7 (myosin light-chain kinase inhibitor) each displayed effects additive to CB (1) [75]. In any case, the results indicated that an increased drug concentration causes morphological changes ranging from inhibition of membrane ruffling to the induction of cell rounding, with the only exception of chaetoglobosin K (ChK, 59) being ineffective on the latter.…”
Section: Correlating Cytochalasan Chemodiversity With the Activity Sp...supporting
confidence: 81%
“…Recent studies have shown that the Rho/myosin light chai (MLC) signaling pathway critically regulated the fenestra morphogenesis of LSECs and enhanced Rho/MLC activity could lead to enlarged fenestra size of LSECs. 44 The levels of active RhoA (RhoA-guanosine triphosphate [GTP]) and active MLC (pMLC) were significantly increased in Adamts18 −/− LSECs ( Figures 6 B and 6C). VEGFA also regulates cytoskeletal changes through Src and RhoA to activate YAP/TAZ.…”
Section: Resultsmentioning
confidence: 99%
“…found that MLC phosphorylation promoted actomyosin contraction at the edge of the sieve plate, leading to the increase of the fenestration diameter. 44 In the primary isolated Adamts18 −/− LSECs, the downstream of VEGFA signaling pathway is significantly changed, including enhanced Src phosphorylation, RhoA activation, and MLC phosphorylation. VEGFA mediates cytoskeleton to activate YAP/TAZ, which enters the nucleus and initiates transcriptional procedures, further regulating cytoskeleton to affect permeability.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the loss of this receptor was associated with the suppression of proteins involved in the intracellular vesicle transport apparatus for removal of large molecules and nanoparticles from the blood and the metabolic/catabolic processes of these scavenged molecules [7,26]. Likewise, the 63 common up-regulated proteins were related to the activation of pathways associated with the actin-dependent cytoskeleton reorganization regulated by Rho and controlling LSEC fenestration [27,28]. LSEC, having lost the CD32b receptor, showed a potent activation of proteins that modulate the cytoskeleton and the polymerization/depolymerization of actin filaments associated with hepatic stellate cell activation and proteins regulating the immune response.…”
Section: Discussionmentioning
confidence: 99%